Distinct patterns of adult transport-related physical activity (TRPA) behaviour exist independent of the TRPA behaviours of childhood: the childhood determinants of adult health study - Jack T. Evans; Marie-Jeanne Buscot; Seana Gall; Terence Dwyer; Alison Venn; Verity Cleland (BMC, 2023)
Abstract Background Transport-related physical activity (TRPA) is recognised as a potential means of increasing total physical activity participation that may yield substantial health benefits. Public health campaigns focusing on promoting TRPA from a young age aim to develop life-long healthy habits. However, few studies have examined how TRPA changes across the lifecourse and whether childhood TRPA levels influence those observed later in life. Methods Using the Australian Childhood Determinants of Adult Health study (baseline, 1985), latent class growth mixture modelling with adjustment for time-varying covariates was performed using four timepoints (ranging from 7 to 49 years) to assess behavioural patterns and retention of TRPA across the lifecourse. As child and adult adjusted TRPA measures could not be harmonised, trajectories of adult TRPA (n = 702) were instead identified, and log-binomial regression analysis was performed to determine whether childhood levels of TRPA (high/medium/low) influenced these trajectories. Results Two stable groups of adult TRPA trajectories were identified: persistently low (n = 520; 74.2%), and increasingly high TRPA (n = 181; 25.8%). There was no significant relationship between childhood TRPA levels and patterns in adulthood (relative risk of high childhood TRPA yielding high adult TRPA trajectory membership = 1.06; 95% confidence interval = 0.95-1.09). Conclusion This study found childhood TRPA levels were not associated with TRPA patterns in adulthood. These findings suggest that while TRPA in childhood may have health, social, and environmental benefits, it does not appear to impact adult TRPA directly. Therefore, further intervention is required beyond childhood to promote the implementation of healthy TRPA behaviours into adulthood.